Effect of Long Term Exclosure on Changes in Dune Vegetation - Shankar, Vinod; Dadhich, N K (Annals of Arid Zone, 2016)
Experimental evidences indicated that protection led to improvement In the species diversity and richness. Marked improvement in the botanical composition, relative frequency and relative cover of herbs and shrubs was also noticed on the top, the slope and at the base of protected dune. Protected dune was rich in species of higher ecological status e.g. Calligonum polygonoides, Panicum antidotale and Sericostoma pauciflorum etc. Mobile barchan dunes supported under-shrubs of lower ecological status e.g. Cratalaria burhia and Aerva persica was almost devoid of grassy vegetation. Wind seems to be a major ecological factor in the distribution of species to windward and leeward side of the dune. Protection also improved herbage yield.